Pharmacokinetics of sifuvirtide, a novel anti-HIV-1 peptide, in monkeys and its inhibitory concentration in vitro - Dai Shu-jia; Dou Gui-fang; Qian Xiao-hong; Song Hai-feng; Tang Zhong-ming; Liu De-sheng; Liu Xiu-wen; Yang Liu-meng; Zheng Yong-tang; Liang Qing (Acta Pharmacologica Sinica, 2016)
Aim: To study the pharmacokinetics of sifuvirtide, a novel anti-human immunodeficiency virus (HIV) peptide, in monkeys and to compare the inhibitory concentrations of sifuvirtide and enfuvirtide on HIV-1-infected-cell fusion. Methods: Monkeys received 1.2 mg/kg iv or sc of sifuvirtide. An on-line solid-phase extraction procedure combined with liquid chromatography tandem mass spectrometry (SPE-LC/MS/MS) was established and applied to determine the concentration of sifuvirtide in monkey plasma. A four-127I iodinated peptide was used as an internal standard. Fifty percent inhibitory concentration (IC50) of sifuvirtide on cell fusion was determined by co-cultivation assay. Results: The assay was validated with good precision and accuracy. The calibration curve for sifuvirtide in plasma was linear over a range of 4.88–5000 mug/L, with correlation coefficients above 0.9923. After iv or sc administration, the observed peak concentrations of sifuvirtide were 10 626plusminus2 886 mug/L and 528plusminus191 mug/L, and the terminal elimination half-lives (T1/2) were 6.3plusminus0.9 h and 5.5plusminus1.0 h, respectively. After sc, Tmax was 0.25–2 h, and the absolute bioavailability was 49%plusminus13%. Sifuvirtide inhibited the syncytium formation between HIV-1 chronically infected cells and uninfected cells with an IC50 of 0.33 mug/L. Conclusion: An on-line SPE-LC/MS/MS approach was established for peptide pharmacokinetic studies. Sifuvirtide was rapidly absorbed subcutaneously into the blood circulation. The T1/2 of sifuvirtide was remarkably longer than that of its analog, enfuvirtide, reported in healthy monkeys and it conferred a long-term plasma concentration level which was higher than its IC50 in vitro.